eSport Building Design Role In Introducing Its Activities - Y E Sutantio; E Poedjioetami; W W Widjajanti (Institut Teknologi Sepuluh Nopember, 2018)
esport has the meaning of electronic sports, which the aspect of the sport is all facilitated by the electronic system. The definition of esport is a sport that does not compete physically, but is more concerned with strategy and competed online via computer, so players from each team can compete without face to face. In its development, esport enthusiasts from year to year increase, but unfortunately this is not balanced with the existence of facilities that can support the development of esport. Some facilities are often used is a place with different functions. There is still no building with a special function that is used for esport activities. The purpose of this research is to create a building facility that can accommodate the esport activities. Use method / application micro-concept of form is transformative, dynamic macro concept, and modern architectural theme, Result of building design that can present the function esport visually. So that building can be characteristic for esport building.